Potential synergistic effects of lenvatinib and aspirin in aortic dissection: a case report and literature review - Luo, Lan; Liang, Hao; Yuan, Lin; Wu, Ya-Kun (Frontiers in Oncology, 2025)
BackgroundAlthough numerous anticancer drugs targeting vascular endothelial growth factor (VEGF) are commonly used in clinical practice, life-threatening drug-drug interactions (DDIs) involving these drugs are rarely reported.Case summaryA male patient had been taking aspirin for two years following a stroke. He was subsequently diagnosed with hepatocellular carcinoma (HCC) and initiated lenvatinib therapy. Shortly after, he developed lenvatinib-induced hypertension (191/102 mmHg) and was prescribed amlodipine for blood pressure control. At his first routine follow-up for HCC treatment, he was asymptomatic but was incidentally diagnosed with acute aortic dissection (AD). The patient declined endovascular treatment, and his AD lesions remained temporarily stable. Although lenvatinib is generally considered a safe and effective option for advanced HCC, this case raises concerns about a potential link between lenvatinib and aspirin in the development of AD due to their temporal association. This case highlights the need for increased clinical awareness regarding possible DDIs between these two drugs, particularly in patients with untreated acute AD.ConclusionThe concurrent use of lenvatinib and aspirin may increase the risk of AD in patients with cancer. To prevent life-threatening complications, patients receiving both therapies should be closely monitored and strictly adhere to treatment guidelines. For patients who decline invasive AD treatment, continued lenvatinib therapy might be a cost-effective option to improve prognosis, though the continuation of aspirin therapy requires careful consideration.